Congregational Perceptions of the Importance of Personal Testimony in GMIM Getsemani Perum Risky: Persepsi tentang Pentingnya Kesaksian Pribadi di Jemaat GMIM Getsemani Perum Risky - Stoner Wendur; Jessilian Daliaha; Kenneth Lintang; 4d Evi Stans Evlin Tumiwa; Hendry C. M. Runtuwene; Rivay Palempung; Riedel Ch. Gosal (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study explores the perceptions and practices of personal testimony among adolescents and young adults in GMIM Getsemani Perum Risky with regard to their congregational life practices. Using a qualitative participatory ethnographic design, data were gathered from 20 members through in-depth interviews, participant observation, and analysis of congregational documents. The evidence indicates that personal testimony is an essential, not marginal, practice since whoever is to express, interpret, and communicate faith. Testimonies come mostly from a feeling of gratitude at how God has helped them and an inner sense of calling and encouragement from leaders and peers, but they are also accompanied by anxiety, feelings of unworthiness, and fear of being judged. As a matter of fact, empirically, testimony is a kind of lived narrative theology: through telling detailed accounts of the struggle, divine assistance and change, participants re-read their histories of life through the lens of the gospel and combine the teaching of theology with the experience. The act of testifying brings about emotional and spiritual change, while listening to the testimonies of others brings about mutual edification, consolation, and hope. The study further shows that the practice of testifying in this congregation is influenced by the dialogue between GMIM's Reformed heritage and Minahasan cultural values such as mapalus, honesty, and solidarity, which together foster authenticity, openness, and communal responsibility.